2019
DOI: 10.4172/pharmaceutical-sciences.1000489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective Activity of Zanthoxylum armatum on Paracetamol-induced Liver Toxicity in Rats

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 3.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The formation of free radicals (FRs) will be more effective in several diseases through liver toxicity. The developed FRs are unbalanced molecules, during their stabilization alter the physiological function of organs, including liver functions, by reacts with stable molecules and finally lead to oxidative stress (OS) [27,40,41]. The OS can cause unusual diseases like lipid peroxidation, DNA damage, atherosclorosis, cancers, neurodegenerative, inflammatory bowel diseases and accelerated aging [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of free radicals (FRs) will be more effective in several diseases through liver toxicity. The developed FRs are unbalanced molecules, during their stabilization alter the physiological function of organs, including liver functions, by reacts with stable molecules and finally lead to oxidative stress (OS) [27,40,41]. The OS can cause unusual diseases like lipid peroxidation, DNA damage, atherosclorosis, cancers, neurodegenerative, inflammatory bowel diseases and accelerated aging [42].…”
Section: Resultsmentioning
confidence: 99%
“…The collected samples were centrifuged without any delay at 2400rpm/15 min. The separated serum was used to evaluate the liver function parameters such as Aspartate aminotransferase (SGOT), alanine aminotransferase (SGPT), Alkaline phosphatase (ALP) and total bilirubin levels using an auto analyzer [4,27].…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…In a different study, the EE of bark of Z. armatum significantly expressed hepatoprotective activity at concentrations of 100, 200, and 400 mg/kg when administered orally in Wistar albino rats (where liver damage was instigated by paracetamol) by decreasing the levels of hepatic enzymes, bilirubin and at the same time increasing catalase, superoxide dismutase, and glutathione in comparison to silymarin [88]. In a recent study the ME at a dose of 500 mg/kg exhibited successful hepatoprotective activity with 66.87, 64.84, 67.95, 60.76, and 65.85% protection on aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total bilirubin, and total protein enzyme levels of the liver, respectively in Wistar rats [89].…”
Section: Hepatoprotective Activitymentioning
confidence: 97%
“…This protection was evidenced by the modulation of parameters of liver status in serum and histological examinations of hepatic tissues of rats that received the extract. In addition, ethyl acetate, chloroform, and methanol extracts of Z. armatum root were evaluated for their ability to prevent paracetamol-mediated hepatic damage in rats and results showed that methanol extract showed the highest hepatoprotective activity, which was related to its high total phenolic content compared to other extracts [ 177 ]. Activity-guided fractionation identified lupeol as the active ingredient responsible for the hepatoprotective effects of the methanol extract [ 177 ].…”
Section: Health-related Bioactive Properties Of Zanthoxylum Speciesmentioning
confidence: 99%
“…In addition, ethyl acetate, chloroform, and methanol extracts of Z. armatum root were evaluated for their ability to prevent paracetamol-mediated hepatic damage in rats and results showed that methanol extract showed the highest hepatoprotective activity, which was related to its high total phenolic content compared to other extracts [ 177 ]. Activity-guided fractionation identified lupeol as the active ingredient responsible for the hepatoprotective effects of the methanol extract [ 177 ]. The hepatoprotective effects of different parts of Z. armatum could be linked to their strong antioxidant activities [ 86 ].…”
Section: Health-related Bioactive Properties Of Zanthoxylum Speciesmentioning
confidence: 99%